Pemikiran Al-Raghib Al-Asfahani tentang Al-Qur'an, Tafsir dan Ta'wil - Wahyuni Shifatur Rahmah (LPPM IAINU Kebumen, 2020)
The Qur'an is the core texts in the history of Arab civilization. Because the Qur’an uses Arabic, one of the medieval thinkers of the Qur’an, Al-Raghib al-Asfahani, focused his research on the essence of the Qur’an and its character as a language text. This study focuses on al-Asfahani's views on the Qur'an, Tafsir and Ta'wil. Through the description of the analysis of this research shows that Al-Asfahani tried to understand the Qur'an through deepening the Arabic language through his work mu'jam al-Mufradat li Alfaz al-Qur'an. For al-Asfahani, the most important means of understanding the Qur'an is through mastery of language. Because the Qur'an as a great book in Arabic, with its wonderful literary influence. More specifically, He describes the verses of the Qur'an through the mufradat (vocabulary) of the words and the meanings it shows according to the placement of the words in the sentence sequence. So do not depart from a verse and then peeled through the study of language, but the method used is to determine the vocabulary or key words in the Qur'an and then connected with the pieces of verses that contain the same word.